The influence of soldering process parameters on the optical and thermal properties of power LEDs. Issue 4 (7th August 2020) - Ptak, Przemysław; Górecki, Krzysztof; Skwarek, Agata; Witek, Krzysztof; Tarasiuk, Jacek
Abstract : Purpose: This paper aims to present the results of investigations that show the influence of soldering process parameters on the optical and thermal parameters of power LEDs. Design/methodology/approach: The power LEDs were soldered onto metal core printed circuit board (MCPCB) substrates in different soldering ovens: batch and tunnel types, characterized by different thermal profiles. Three types of solder pastes based on Sn99Ag0.3Cu0.7 with the addition of TiO2 were used. The thermal and optical parameters of the diodes were measured using classical indirect electrical methods. The results of measurements obtained were compared and discussed. Findings: It was shown that the type of oven and soldering thermal profile considerably influence the effectiveness of the removal of heat generated in the LEDs tested. This influence is characterized by thermal resistance changes. The differences between the values of this parameter can exceed 20%. This value also depends on the composition of the soldering paste. The differences between the diodes tested can exceed 15%. It was also shown that the luminous flux emitted by the diode depends on the soldering process used. Practical implications: The results obtained could be useful for process design engineers for assembling power LEDs for MCPCBs and for designers of solid-state light sources. Originality/value: This paper presents the results of investigations into the influence of the soldering profiles and soldering pastes used on the effectiveness of the removal of heat generated in power LEDs. It shows and discusses how the factors mentioned above influence the thermal resistance of the LEDs and optical parameters that characterize the light emitted.